Knowledge, attitude, perception, and preventative practices towards COVID-19 in sub-Saharan Africa: A scoping review. - Ugochinyere Ijeoma Nwagbara; Emmanuella Chinonso Osual; Rumbidzai Chireshe; Obasanjo Afolabi Bolarinwa; Balsam Qubais Saeed; Nelisiwe Khuzwayo; Khumbulani W Hlongwana (PLoS ONE)
Background Knowledge, attitudes, perception, and preventative practices regarding coronavirus- 2019 (COVID-19) are crucial in its prevention and control. Several studies have noted that the majority of people in sub-Saharan African are noncompliant with proposed health and safety measures recommended by the World Health Organization (WHO) and respective country health departments. In most sub-Saharan African countries, noncompliance is attributable to ignorance and misinformation, thereby raising questions about people's knowledge, attitudes, perception, and practices towards COVID-19 in these settings. This situation is particularly of concern for governments and public health experts. Thus, this scoping review is aimed at mapping evidence on the knowledge, attitudes, perceptions, and preventive practices (KAP) towards COVID-19 in sub-Saharan Africa (SSA). Methods Systematic searches of relevant articles were performed using databases such as the EBSCOhost, PubMed, Science Direct, Google Scholar, the WHO library and grey literature. Arksey and O'Malley's framework guided the study. The risk of bias for included primary studies was assessed using the Mixed Method Appraisal Tool (MMAT). NVIVO version 10 was used to analyse the data and a thematic content analysis was used to present the review's narrative account. Results A total of 3037 eligible studies were identified after the database search. Only 28 studies met the inclusion criteria after full article screening and were included for data extraction. Studies included populations from the following SSA countries: Ethiopia, Nigeria, Cameroon, Uganda, Rwanda, Ghana, Democratic Republic of Congo, Sudan, and Sierra Leone. All the included studies showed evidence of knowledge related to COVID-19. Eleven studies showed that participants had a positive attitude towards COVID-19, and fifteen studies showed that participants had good practices towards COVID-19. Conclusions Most of the participants had adequate knowledge related to COVID-19. Despite adequate knowledge, the attitude was not always positive, thereby necessitating further education to convey the importance of forming a positive attitude and continuous preventive practice towards reducing contraction and transmission of COVID-19.